The Effect Of The Team Assisted Individualization Type Cooperative Learning Model Assisted By Pop-Up Book Media On Creativity In Learning Science In Grade III Of SDN - Adawiah, Rabiatul; Selvi, Nurhayati; Nur Fajrin, Syarifah (ALENA : Journal of Elementary Education, 2025)
This study aims to determine: 1) description of the cooperative learning model of Team Assisted Individualization type assisted by Pop-Up Book media for third grade students of SDN 222 Inpres Pao-Pao, Maros Regency, 2) description of student learning creativity using the cooperative learning model of Team Assisted Individual ization type assisted by Pop-Up Book media for third grade students of SDN 222 Inpres Pao-Pao, Maros Regency, 3) influence on student learning creativity after using the cooperative learning model of Team Assisted Individualization type assisted by Pop Up Book media for third grade students of SDN 222 Inpres Pao-Pao, Maros Regency. This type of research is experimental research with a one group pretest-posttest design with a sample size of 22 students consisting of 7 boys and 15 girls using observation sheet instruments, questionnaires and documentation. In this study using descriptive statistical analysis and inferential analysis with the help of SPSS version 26. The results of this study indicate that the effect of the cooperative learning model type Team Assisted Individualization assisted by Pop-Up Book media on IPAS learning creativity, through the stages of placement tests, teams, teaching groups, team studies, whole class units, fact tests, and team scores in class III 222 Inpres Pao-Pao Maros Regency has been well implemented. The picture of learning creativity is dominant in the moderate and good categories where each shows a frequency of 8 out of a total of 22 students in the 40-41 and 38-39 score ranges. The use of cooperative learning model of Team Assisted Individualization type assisted by Pop-Up Book media has an effect on IPAS learning creativity in class III of SDN Inpres Pao-Pao Maros Regency with a 2-tailed significance value of 0.000